Ectopic Pregnancy Within a Cesarean Section Scar: Report of Two Cases - Fang-Yi Chen; Pao-Ling Torng; Su-Cheng Huang; Song-Nan Chow (Elsevier, 2004)
Objective: Ectopic pregnancy embedded in a previous cesarean section scar is rare. We report two cases of cesarean section scar pregnancy managed with conservative treatment. Case Reports: The first patient was a 39-year-old woman who presented with vaginal spotting and delayed menstruation. She had undergone two previous cesarean sections and was found to be at 5 weeks' gestation. The second patient was a 38-year-old woman with one previous cesarean section. She presented with vaginal bleeding and abdominal fullness and was found to be at 7 weeks' gestation. In both cases, cesarean section scar pregnancies were diagnosed by transvaginal sonography. Intragestational sac injection of methotrexate (MTX) 50 mg was administered under transabdominal sonographic guidance, followed by multiple doses of intramuscular MTX. Serum β-human chorionic gonadotropin levels declined gradually and reabsorption of the gestational sacs was confirmed by sonography. Conclusion: Early detection of cesarean section scar pregnancy allowed the choice of several conservative treatment options. Intragestational sac injection of MTX followed by systemic MTX was effective in terminating the ectopic pregnancy, even after a fetal heartbeat was detected.